2009
DOI: 10.3171/2008.5.17557
|View full text |Cite
|
Sign up to set email alerts
|

Gliadel (BCNU) wafer plus concomitant temozolomide therapy after primary resection of glioblastoma multiforme

Abstract: Object Gliadel (BCNU) wafer and concomitant temozolomide (TMZ) therapy, when used individually as adjuvant therapies, extend survival from that achieved by resection and radiation therapy (XRT) for glioblastoma multiforme (GBM). It remains unstudied whether combining Gliadel and TMZ therapy is safe or further improves survival in patients with newly diagnosed GBM. The authors reviewed their initial experience utilizing combined Gliadel, TMZ, and radiation therapy for the treatment of GBM. Methods All cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(165 citation statements)
references
References 21 publications
(33 reference statements)
2
156
0
7
Order By: Relevance
“…Localized drug delivery devices provide high drug concentrations to the tumor site while preventing drug degradation and clearance until its release (7,8). The efficacy of current intracranial drug delivery, such as Carmustine wafers, has promise, with a doubling of median survival from 9 to 20 mo in the case of Carmustine wafers (6,9,10). Phase III trial data indicated a 2-to 3-mo survival advantage in Carmustine wafers-treated patients (11), and Carmustine wafers continue to have a role combined with radiation and oral temozolomide (TMZ).…”
mentioning
confidence: 99%
“…Localized drug delivery devices provide high drug concentrations to the tumor site while preventing drug degradation and clearance until its release (7,8). The efficacy of current intracranial drug delivery, such as Carmustine wafers, has promise, with a doubling of median survival from 9 to 20 mo in the case of Carmustine wafers (6,9,10). Phase III trial data indicated a 2-to 3-mo survival advantage in Carmustine wafers-treated patients (11), and Carmustine wafers continue to have a role combined with radiation and oral temozolomide (TMZ).…”
mentioning
confidence: 99%
“…tarafından bu protokol ile tedavi edilen 33 hastada medyan sağkalım yaklaşık 20.7 ay ve iki yıllık sağkalım %36 bulunmuştur. [23] Bu sağkalım avantajı başka geriye dönük çalışmalarda da ortaya konmuştur. [24] Lokal ve sistemik tedavi kombinasyonu umut verici görünmekle birlikte standart olarak uygulanabilmesi için daha fazla ileriye yönelik çalışmaya ihtiyaç vardır.…”
Section: Discussionunclassified
“…A retrospective study of 33 patients who received carmustine wafers in addition to standard chemoradiation suggested that the treatments can be combined safely. The median survival duration of these patients, who, by definition, all had extensive surgical debulking, was nearly 21 months [17]. A large prospective randomized trial is needed to clearly document the added survival benefit of carmustine wafers to standard therapy in this patient population.…”
Section: How Should Other Fda-approved Therapies (Such As Carmustine mentioning
confidence: 99%